Verbal Abuse Dalam Permainan Mobile Legends Intensitas, Bentuk, Penyebab, dan Sikap - Rini Rini (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Mobile Legends is one of the most popular online games in Indonesia. Unfortunately, manyMobile Legends players do verbal abuse during the game. The intensity, form, reasons forverbal abuse and attitudes in dealing verbal abuse in this game need to be explored. Thesampling technique used is accidental sampling. Participants in this study were 60 peoplewho were given a questionnaire in the form of open-ended questions, and 15 people whowere in-depth interview. Data analysis using descriptive qualitative approach. The resultsof the analysis show that: 1). more players become victims than perpetrators of verbalabuse, 2). Types of verbal abuse are divided into two, namely verbal abuse which is relatedto the skill to play and which is not related to the skill to play, 3). Most of the participants'attitudes chose not to care about verbal abuse and turned off the comment column, 4). Thereasons for verbal abuse during game preparation are due to mistakes in banning andchoosing heroes, and not having skins, while during the game it is due to bad gameperformance, handling teammates' buffs, not helping the team and getting out of the game.